2018
DOI: 10.1111/ajfs.12235
|View full text |Cite
|
Sign up to set email alerts
|

Cash Holdings Adjustment Speed and Managerial Ability

Abstract: Using the partial adjustment model of cash holding, we find that managerial ability is negatively related to adjustment speed of cash holdings toward the target, particularly when the firm has excess cash. We also find that the relation between managerial ability and cash holding adjustment speed is weaker in the presence of the internal capital market. Additionally, we provide evidence that firms with higher managerial ability are less likely to make inefficient investments when they have excess cash, implyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…Although reaching the optimal capital structure may be one way to increase firm value, managers with better abilities may focus on operational decisions that maximize firm value rather than spend their limited time and efforts on capital structure decisions. Similar to our findings, recent research by Cho et al (2018) reported slower adjustment speeds of cash holdings toward the target level for more competent managers. Both studies cast doubt on the conventional "optimal" level in the partial adjustment models.…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…Although reaching the optimal capital structure may be one way to increase firm value, managers with better abilities may focus on operational decisions that maximize firm value rather than spend their limited time and efforts on capital structure decisions. Similar to our findings, recent research by Cho et al (2018) reported slower adjustment speeds of cash holdings toward the target level for more competent managers. Both studies cast doubt on the conventional "optimal" level in the partial adjustment models.…”
Section: Introductionsupporting
confidence: 92%
“…Koester et al (2017) find the positive relation between managerial ability and tax avoidance. Cho et al (2018) present that more competent managers accumulate cash holdings to engage in more efficient investment decisions, resulting in slower cash adjustment speed toward the target.…”
Section: Literature On Managerial Abilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Following the trade-off, pecking order and free cash flow theories [1], a plethora of research focused on the determinants of firms' cash holdings (Al-Najjar, 2013;Ferreira and Vilela, 2004;Guizani, 2017;Opler et al, 1999), the existence of firms' target cash holdings and firms' tendency to adjust toward the optimum target (Cho et al, 2018;Faulkender and Wang, 2006). However, a topic that is still not fully understood is the relationship between firms' cash holdingsespecially levels of cash holdingsand their performance.…”
mentioning
confidence: 99%